2018
DOI: 10.3928/1081597x-20180124-01
|View full text |Cite
|
Sign up to set email alerts
|

Early Tomographic Changes in the Eyes of Patients With Keratoconus

Abstract: Early stages of keratoconus are hard to diagnose and best results can be achieved by using index of height decentration and index of vertical asymmetry. As the disease progresses, D-index is better suited to diagnose an ectasia. Astigmatism, keratometry, and pachymetry barely change in the early stages, so these values are not as fitting as corneal elevation parameters for early diagnosis. [J Refract Surg. 2018;34(4):254-259.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 25 publications
(11 reference statements)
4
13
0
4
Order By: Relevance
“…Hwang et al [7] proposed a first model based on the combination of five metrics (AUC: 0.86, Sensitivity: 83%, Specificity: 83%). Similar results have been obtained by other authors [5,6,20] in the model development phase and based on the exclusive metrics of the same Scheimpflug technology. In contrast, our study obtained higher performance values for model development (AUC: 0.95) and similar ones in the validation phase (AUC: 0.85), and was composed of metrics that are not exclusive to the same Scheimpflug technology.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hwang et al [7] proposed a first model based on the combination of five metrics (AUC: 0.86, Sensitivity: 83%, Specificity: 83%). Similar results have been obtained by other authors [5,6,20] in the model development phase and based on the exclusive metrics of the same Scheimpflug technology. In contrast, our study obtained higher performance values for model development (AUC: 0.95) and similar ones in the validation phase (AUC: 0.85), and was composed of metrics that are not exclusive to the same Scheimpflug technology.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported similar results to ours about models based on Scheimpflug metrics [5][6][7]20]. Hwang et al [7] proposed a first model based on the combination of five metrics (AUC: 0.86, Sensitivity: 83%, Specificity: 83%).…”
Section: Discussionsupporting
confidence: 79%
“…Out of all deviation from normality indices, final D showed the best repeatability (RR = 12.91%) as well as excellent reliability (ICC = 0.994). While total D has been recommended as a valuable parameter in the detection 14,15 and evaluation of ectatic progression in previous studies, especially in early stages of keratoconus 16 , in this study, while performing quite well, it did overall rank lower than other measured parameters in terms of accuracy in repeated exams.…”
Section: Discussionmentioning
confidence: 51%
“…They found that nearly all 27 of the eyes had a progression in the posterior cornea elevation whereas the keratometry and pachymetry did not necessarily change between the 2 measurement points. 4 It is possible that keratoconus eyes could have been erroneously labeled as the unaffected AKC eyes (D-index ¼ 1.56AE0.79) in the present study, 1 resulting in a more "advanced form" of subclinical keratoconus in the current study cohort. This could have reduced the impact of the posterior corneal elevation, which is particularly relevant for the diagnostic sensitivity in the early stage of the disease.…”
mentioning
confidence: 84%
“…Despite applying these quantitative cutoffs, some of the 94 very asymmetric ectasia with normal topography eyes were still regarded to have a suspicious curvature map. 3 A recent study by Shajari et al 4 performed sequential measurements in 27 fellow eyes of unilateral keratoconus, which have not yet shown any ectatic changes. The D-index changed from 0.91AE0.39 to 1.48AE0.45 between the 2 measurements separated by a mean duration of 360AE246 days.…”
mentioning
confidence: 99%